Moments of Risk: Identifying Threats to Electronic Records - Bearman, David A. (Archivaria, 2007)
The author left the field of electronic records a decade ago, and has returned to survey the landscape of what at that time appeared to be a battleground of irreconcilable positions. Since 1997, significant areas of agreement seem to have emerged. This paper identifies six agreed “moments of risk,” which occur at critical state transitions in the life of records: at capture, maintenance, ingestion, access, disposal, and preservation. It examines the literature of the past decade to identify the commonly held criteria by which records can be known to have survived such moments of risk unscathed. By locating widely accepted critical points in the life of records and the criteria by which we can assure ourselves that our management methods have succeeded, it hopes to make way for tests that could be agreed between proponents of different strategies. RÉSUMÉ L’auteur a quitté le domaine des documents électroniques il y a dix ans, puis il y est retourné afin d’examiner ce qui à l’époque semblait être un champ de bataille de positions irréconciliables. Depuis 1997, des points de convergence significatifs semblent être ressortis. Ce texte identifie six « moments de risque » qui se produisent lors de transitions d’états critiques dans la vie des documents : l’enregistrement, le maintien, l’ingestion, l’accès, la disposition et la préservation. Il examine la littérature de la dernière décennie dans le but d’identifier les critères généralement reconnus selon lesquels on peut savoir que les documents ont réussi à traverser ces moments de risqué indemnes. En repérant les points critiques dans la vie des documents et les critères selon lesquels nous pouvons nous assurer que nos méthodes de gestion ont réussi, il espère préparer l’arrivée de tests qui pourraient être acceptés par les défenseurs de différentes stratégies.